Governance and Economic Evaluation of Governance: Turkey’s Good Governance Indicators - Yürükoğlu, Buse (Journal of Applied And Theoretical Social Sciences, 2021)
Today, although governance is important for every country, it is of great importance in solving economic and social problems especially in developing countries. Many studies in the literature reveal that the understanding of governance affects the economic performance of countries positively. In this context, it is possible to evaluate countries comparatively by considering the effects of their governance quality on national economies. In this study, it is aimed to emphasize that the countries that are in a good position in terms of governance indicators are generally more successful in sustainable economic growth and development, and it has been tried to show that institutional differences are effective on the development gap between countries. In this study, the role of governance on economic growth and development was discussed and comparisons were made between Turkey and G7 countries based on the governance indicators in The Worldwide Governance Indicators (WGI) of the World Bank and economic performance data obtained from the World Bank. Governance indicators and macroeconomic data obtained from the World Bank are tabulated and the current situation of Turkey and G7 countries is interpreted. Significant differences were observed in the comparisons made. G7 countries have high scoring governance indicators that can produce positive economic results. On the other hand, Turkey's economic and governance indicators lag behind the averages of developed countries.